Contact Centre Service Excellence: A Proposed Conceptual Framework - Dharamdass, Surya; Fernando, Yudi (Inderscience Enterprises Ltd., 2018)
This paper aims to develop a proposed conceptual framework that can be used in studying the determinants of contact centre service excellence for the continuously growing contact centre business globally. A content analysis method is performed on a range of English-written published papers between 1993 and 2014 to explore the proposed determinants of contact centre service excellence. The primary observation shows that there is limited academic literature in this area. The findings from the distillation of the proposed determinants of contact centre service excellence in essence suggest that there should be a high focus on the people - customer service agents (CSAs) hiring criteria, training and development, reward system, team structure and the cross-functional coordination process. The implication to future researchers is to focus on these determinants to better understand the impact on service excellence. For practitioners, the implication is to consider reviewing the current determinants used in their organisations to achieve service excellence and consider adopting the proposed determinants